First Record of Rhynchotermes nasutissimus (Silvestri) (Isoptera: Syntermitinae) Associated with Rat Carrion in Brasília, Brazil - Prestes, Anna Carolina; Tepedino, Karla Pessôa; Kosmann, Cecília; Pujol-Luz, José Roberto (EntomoBrasilis, 2014)
Rhynchotermes nasutissimus (Silvestri) is a leaf litter feeder species distributed through the Neotropical region. We found for the first time this species associated with rat carrion in an urban area of Brasília, Distrito Federal, Brazil. Ten soldiers and 36 workers were spread in the cavities and between internal leathers of the carrion’s dry remains of the animal that have been exposed during a week in the soil, in March 2012, at end of the wet season. We believe that this uncommon behavior may reflect a nutritional need. Primeiro Registro de Rhynchotermes nasutissimus (Silvestri) (Isoptera: Syntermitinae) Associado à Carcaça de Rato em Brasília, Brasil Resumo. Rhynchotermes nasutissimus (Silvestri) é uma espécie que se alimenta de folhas de serrapilheira, distribuída pela região Neotropical. Encontrou-se pela primeira vez esta espécie associada com carcaça de rato, em uma área urbana de Brasília, Distrito Federal, Brasil. Os dez soldados e 36 operários se encontravam dispersos entre as vértebras e restos secos do animal que foi exposto durante uma semana no solo em março de 2012, final da estação chuvosa. Acredita-se que este comportamento raro seja resultado de alguma deficiência nutricional.